Letras de San Nicolás: estudio exploratorio y descriptivo del repertorio tipográfico rotulado presente en el barrio San Nicolás de la ciudad de Cali en 2017 (2019)
San Nicolás is a meeting point for many crafts and services related to graphic design. Nowadays, the lettering present in the streets of this historic Cali neighborhood is a clear example of how written language manifests itself in everyday life without major mediations, seeking an apparently communicative function, but that hides a decision-making, conscious design component towards the exercise, which deserves to be studied. The purpose of this research is to be able to generate an approximation to the analogue, handwritten, lettered typographical manifestations, which have been generated within it